FANDOMAT: REVERSE VENDING MACHINE - Kozhanov, Sanzhar; Kenzhebek, Daryn (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The overwhelming production of plastics, with an estimated 6.3 billion tonnes manufactured globally from 1950 to 2018, has led to a dire environmental crisis. A minimal fraction of this plastic has been recycled or incinerated, leaving a significant impact on the environment and public health. The improper disposal and burning of plastic release toxic substances such as phthalates, heavy metals, and bisphenol A into food, water, and the air, posing severe risks to living organisms. Additionally, the durability of plastics contributes to marinepollution, where they degrade into microplastics that harm marine life. Addressing this issue requires legislative measures to limit plastic waste and regulate the use of harmful additives. The plastics industry must take responsibility for the lifecycle of its products through recycling or upgrading programs. Innovative solutions like Reverse Vending Machines (RVMs), exemplified by the Fandomat, offer a promising approach to mitigate these adverse effects. By incentivizing recycling through monetary rewards for depositing glass, metal, and plastic bottles, RVMs aim to bridge the gap between environmental conservation efforts and community engagement, promoting resource conservation, recycling behaviors, and waste reduction as long-term goals.
Keywords: Type of access: Restricted